Breaking the Anti-Globalization Deadlock: How E-Commerce Negotiations Drive the Reshaping of WTO Multilateral Cooperation - Wen Xiao (Law and Economy, 2024)
Amid rising anti-globalization sentiment, the global trading system faces increasing fragmentation and weakened multilateral cooperation. The World Trade Organization (WTO)’s e-commerce negotiations offer a crucial pathway to address these challenges by establishing digital trade rules and fostering market integration and inclusive development. This paper examines key breakthroughs in the e-commerce negotiations, including progress in data flow governance, tariff policies, and the regulation of emerging technologies, highlighting their role in reshaping multilateral cooperation. Drawing on regional agreements and international collaboration, the study proposes strategies for harmonizing data governance, implementing flexible tariff mechanisms, and improving dispute settlement systems. The findings demonstrate that e-commerce negotiations are a vital tool for the WTO to reform the multilateral cooperation framework, tackle pressing global challenges, and promote re-globalization.